Bladder injury in an incarcerated inguinal hernia in a pediatric patient - Gunadi, Gunadi; Oktavian, Arif; Iskandar, Kristy; Vujira, Khanza Adzkia; Fauzi, Aditya Rifqi (Elsevier, 2022)
Bladder injury is a relatively uncommon side effect of inguinal hernia surgery. One of the causes is bladder ears, i.e., protrusions of the urinary bladder across the deep inguinal ring. Here, we presented a case of bladder injury during inguinal hernia surgery that was found intraoperative and successfully repaired without any sequelae for long-term follow up after surgery. A 10-month-old male came to the emergency department with a chief complaint of swelling and pain on the groin and profuse vomiting. Fluid resuscitation and manual reduction was performed but failed. Therefore, we decided to perform emergency surgery. We accidently opened the bladder during the surgery since mimicking the hernia sac. Fortunately, this injury was found intraoperatively. Subsequently, we repaired the bladder injury, followed by hernia repair. The patient was discharged uneventfully on a post-operative day 7. The patient was regularly followed up for approximately two years after surgery. No sequelae were noted. In conclusions, bladder injury is a rare case that might be occurred during an incarcerated inguinal hernia repair. Surgeons, particularly young surgeons or trainees should be aware of the possibility of bladder ears that might mimic the hernia sac and injured during the hernia repair.